Immune-Related Adverse Events in PD-1 Treated Melanoma and Impact Upon Anti-Tumor Efficacy: A Real World Analysis - Bastacky, Melissa L.; Wang, Hong; Fortman, Dylan; Rahman, Zahra; Mascara, Gerard P.; Brenner, Timothy; Najjar, Yana G.; Luke, Jason J.; Kirkwood, John M.; Zarour, Hassane M.; Davar, Diwakar (Frontiers in Oncology, 2021)
Background: Anti-PD-1 immune checkpoint inhibitor (ICI) therapy has revolutionized the treatment of melanoma by producing durable long-term responses in a subset of patients. ICI-treated patients develop unique toxicities - immune related adverse events (irAEs) – that arise from unrestrained immune activation. The link between irAE development and clinical outcome in melanoma and other cancers is inconsistent; and little data exists on the occurrence of multiple irAEs. We sought to characterize development of single and multiple irAEs, and association of irAE(s) development with clinical variables and impact upon outcomes in advanced melanoma patients treated with anti-PD-1 ICI. Methods: We conducted a retrospective study of 190 patients with metastatic melanoma treated with single-agent anti-PD-1 ICI between June 2014 and August 2020 at a large integrated network cancer center identified through retrospective review of pharmacy records. irAEs were graded based on the Common Terminology Criteria for Adverse Events (CTCAE) version 5.0. Results: 190 patients were evaluated of whom 114 patients (60.0%) experienced >1 irAE, including 30 (15.8%) with grade 3/4 irAEs. The occurrence of any irAE was strongly associated with the development of investigator-assessed response to anti-PD-1 therapy (p<0.0001); whether evaluated by current (p=0.0082) or best (p=0.0001) response. In patients with >2 irAEs, distinct patterns were observed. Median progression-free survival (PFS) and overall survival (OS) were greater in those with any irAE compared to those without (PFS, 28 months vs. 5 months, p < 0.0001; OS, not reached vs. 9 months, p < 0.0001). Development of >2 irAEs had a trend towards improved PFS and OS compared to those who developed a single irAE, although this did not reach statistical significance (p=0.2555, PFS; p=0.0583, OS). Obesity but not age or gender was distinctly associated with irAE development. Conclusions: In this study, we demonstrated that irAE occurrence was significantly associated with response to anti-PD-1 therapy and improved PFS/OS. Those who developed multiple irAEs had a trend towards improved PFS and OS compared to those who developed only a single irAE. Increased BMI but neither age nor gender were associated with irAE development. Distinct patterns of irAEs observed suggest shared etiopathogenetic mechanisms.